Diversity of Angiosperm Flora of Kuakata National Park, Patuakhali District, Bangladesh - Rahaman, M Azizar; Rahman, Md Azizur; Uddin, Mohammad Zashim (Journal of the Asiatic Society of Bangladesh, Science, 2017)
The article mainly highlights the angiosperm diversity of Kuakata National Park (KNP) of Patuakhali district. Angiosperm diversity assessment in the park was conducted in between 2015 and 2016. A total of 265 plant species belonging to 75 families and 204 genera was identified from this National Park. Tree species of the park are represented by 89, shrubs by 45, herbs by 94, climbers by 31 and epiphytes by 6 species. In Magnoliopsida (dicots), Fabaceae is the largest family represented by 14 species, whereas in Liliopsida (monocots), Poaceae is the largest family represented by 13 species. The plant species recorded from the National Park were distributed in different habitats and maximum species were recorded in plantation areas(108) followed by homesteads (61), cultivated land(38), roadsides (35) and mangrove areas (23).The study has reported the presence of medicinal plants, wildlife supporting plants, exotics and invasive plants and rare plants in park. The presence of edible species in the National Park is very rare. The introduction of exotics species into the National Park has been accepted. As the presence of exotics in park, local flora will be faced great challenges in future for their existence. This article also focused conservation values, management concerns and some actions for conservation of angiosperm diversity in the National Park. The present angiosperm diversity assessment in the park is very preliminary and based on this sound conclusion cannot be made yet. Asiat. Soc. Bangladesh, Sci. 43(2): 143-159, December 2017